Examining the relationship between student attitude and academic cheating. Issue 7 (3rd October 2021) - Yu, Hongwei; Glanzer, Perry L.; Johnson, Byron R.
ABSTRACT: Academic cheating has long been persistent and pervasive on college campuses. Informed by the theory of planned behavior (TPB), we studied how factors collectively influence academic cheating among undergraduate students. Consistent with prior research, we found a lack of self-control, attitude toward academic misconduct, subjective norm, and perceived behavioral control relates to college student engagement in academic cheating. Notably, we found that attitude toward academic cheating not only directly relates to student academic cheating but mediates the relationship between lack of self-control and student academic cheating. Given that the attitude toward academic cheating is malleable, such findings have important implications for reducing academic misconduct among college students.